Private-public interaction in public service innovation processes- business model challenges for a start-up EdTech firm. Issue 5 (4th June 2019) - Mattsson, Lars-Gunnar; Andersson, Per
Abstract : Purpose: Contemporary public service innovations to an important degree are initiated and enabled by digitalization. Digitalization stimulates entry of new firms (start-ups) based on innovative implementation of digital technology for public services. The interwoven digitalization and innovation processes involve interaction and interdependencies between private business actors and public service providing actors. In this paper, the authors take the perspective of a start-up business actor that tries to develop and implement a viable business model in the very dynamic context of digital transformation of public education. The purpose of this paper is to analyze how the instability of a startup firm's business model during public service innovation can be explained. The research question is: "How can business modeling by a start-up firm be explained by tensions between its business model and public service provision models?" Design/methodology/approach: Based on an abductive logic, the authors choose a single-case study of a start-up firm's development in 2010-2018 and its interaction with public actors. Information about the firm acquired in the first phase of the study showed that it frequently changed its business model. A general analytical framework was developed to aid in efforts to answer the research question. Findings: The case showed that a business model could be seen as a temporary outcome of a business modeling process, and that also concurrently public actors change their public actors' service provisioning models. Public-private interaction reveals tensions that drive business modeling. Originality/value: The study contributes to empirical knowledge about private-public interaction in the dynamic and complex context in which digital transformation in society drives public service innovations. The conceptual contribution rests more generally in the analytical framework and how it frames public actor's "service provision modeling" as a driver of business modeling.